PUTUSAN PENGADILAN TENTANG MELAWAN HUKUM DALAM TINDAK PIDANA KORUPSI - Nur Basuki Minarno (Perspektif, 2007)
From this research, it is found out that firstly the concept of power belongs to the regime of Administrative Law To prove the element of misuse of power therefore, it is necessary apply legal concept under Administrative Law regime. In practice, however to determine whether there is an element of misuse of power court relies upon principle of reasonableness and carefulness as a parameter that are only suitable to determine materially unlawful act. Doing as such, the court mixes up two parameters of different legal regimes in determine the element of misuse of power.